L’edilizia residenziale pubblica del Novecento alla prova del tempo. La sfida della conservazione di un Patrimonio vivo attraverso il caso di Milano / Twentieth-Century Public Housing at the Test of Time: The Challenge of Preserving a Living Heritage by means of the Milan Case Study - Giambruno, Mariacristina; Pistidda, Sonia; Salis, Laura (Restauro Archeologico, 2025)
The public housing stock built in Italy during the 20th century, from the 1930s through the post-war reconstruction and economic boom, has shaped urban expansion and often remains the only recognizable framework within otherwise unplanned contexts. Despite their architectural value, innovative housing solutions, and experimental materials, these estates are rarely conserved, even though many are now theoretically subject to heritage protection. Current management practices are primarily oriented toward ensuring functionality, safety, and compliance with seismic and energy regulations. This paper reflects on the tension between conservation and transformation, considering public housing as a ‘living heritage’. Starting from case studies in Milan, managed by the municipal company MM S.p.A., it proposes a methodology of study and documentation aimed at balancing the preservation of architectural identity with the necessary upgrading of housing to contemporary standards.